Corrections to “Multi Objective Prioritized Workflow Scheduling Using Deep Reinforcement Based Learning in Cloud Computing” - Sudheer Mangalampalli; Syed Shakeel Hashmi; Amit Gupta; Ganesh Reddy Karri; K. Varada Rajkumar; Tulika Chakrabarti; Prasun Chakrabarti; Martin Margala (IEEE Access)
Presents corrections to the paper, (Corrections to “Multi Objective Prioritized Workflow Scheduling Using Deep Reinforcement Based Learning in Cloud Computing”).